IMPLEMENTASI KETERAMPILAN MENGAJAR DAN MENGELOLA KELAS DALAM PROSES PEMBELAJARAN OLEH GURU DI SD NEGERI 34 BANDA ACEH - Nurhaidah Nurhaidah.; Alfiati Syafrina (Universitas Syiah Kuala, 2020)
Classroom management problems must be addressed with management corrective action, whereas teaching problems must be addressed with instructional corrective action. The teacher's actions can be in the form of preventive measures, namely by providing both physical and socio-emotional conditions so that students feel right with a sense of comfort and safety to learn. Other actions can be in the form of corrective action against the deviant behavior of students and damage the optimal conditions for the ongoing teaching and learning process. The purpose of this study was to describe the implementation of classroom management teaching skills by teachers in the teaching process at SD Negeri 34 Banda Aceh. The approach used in this research is a qualitative descriptive approach. The research subjects were 8 classroom teachers with permanent teacher status. Data collection techniques used observation and interview techniques. After the data collected is analyzed using data reduction, data presentation and conclusions. The results of this study indicate that the implementation of classroom management teaching skills carried out by teachers at SD Negeri 34 Banda Aceh has been carried out effectively and efficiently in the learning process in the classroom. A total of 6 teachers have implemented classroom management in the learning process in an optimal, effective and efficient manner, the creation of learning conditions in the classroom is very conducive and comfortable, learning time is in accordance with the plan, the distribution of attention carried out by the teacher visually and verbally is maximized, able to focus The attention of students to learn individually and in groups and provide reinforcement to students, can arrange class layout and maintain class cleanliness and comfort by adjusting class conditions so that students are comfortable in learning and can create a conducive learning climate. Meanwhile, the other 2 teachers are still not able to carry out the teaching skills to manage the class properly, which is related to the time and the creation of learning conditions in the classroom which are not conducive and comfortable, the distribution of attention made by the teacher visually and verbally is not optimal, and cannot maintain class conditions orderly.